A Collaborative Approach to Policy Strategies for Culturally and Locally Inspired Tourism Packaging in Tomohon City - Obed Bida; Benny Sigiro; Hadirman Hadirman (CV. RADJA PUBLIKA, 2026)
This study examines the implementation of a collaborative approach in culturally and locally inspired tourism packaging policies in Tomohon City, North Sulawesi, Indonesia. The research focuses on the dynamics of cross-sector collaboration and the integration of local cultural values in sustainable tourism governance. A qualitative descriptive case study approach was employed through in-depth interviews, participatory observation, and document analysis involving government institutions, cultural communities, tourism business actors, and local residents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal a transformation from government-centered tourism management toward collaborative governance characterized by active participation among stakeholders. Local cultural values such as mapalus (mutual cooperation) and masendeke (togetherness) function as social and ethical foundations that strengthen trust, coordination, and policy legitimacy. Cultural festivals, heritage preservation programs, and digital tourism innovations have contributed to enhancing destination competitiveness, community empowerment, and socio-economic resilience. The study proposes a “Culturally Embedded Collaborative Governance” model, emphasizing the integration of local wisdom into tourism policy and governance practices. The research contributes to the development of collaborative governance and sustainable tourism literature while offering practical policy recommendations for culturally based tourism development in regional contexts.